Traversing digital Babel information, e-government, and exchange - Peled, Alon 1962- (Information policy series, 2014)
Alon Peled offers a groundbreaking approach for enabling information sharing among public sector agencies: using selective incentives to 'nudge' agencies to exchange information assets